Case Report: Epidural Abscess Following Obstetric Epidural Anesthesia in Vietnam - Nguyen LD; Vo TT; Tran CV; Hoang TT; Vu PX; To KD; Doan HT; Nguyen AD (International Medical Case Reports Journal, 2021)
Lam Duc Nguyen,1 Toan Thanh Vo,2 Cuong Van Tran,1 Tam Thi-Thanh Hoang,1 Phuoc Xuan Vu,3 Kha Dong To,4,5 Ha Thi-Ngoc Doan,1 Anh Duy Nguyen6 1Hanoi Medical University, Hanoi, Vietnam; 2Thong Nhat Hospital, Ho Chi Minh City, Vietnam; 3Bach Mai Hospital, Hanoi, Vietnam; 4School of Medicine, Vietnam National University Ho Chi Minh City, Ho Chi Minh City, Vietnam; 5Vietnam National University Ho Chi Minh City, Ho Chi Minh City, Vietnam; 6Hanoi Obstetrics and Gynecology Hospital, Hanoi, VietnamCorrespondence: Toan Thanh VoThong Nhat Hospital, 1 Ly Thuong Kiet Street, Ward 7 Tan Binh District, Ho Chi Minh City, 700000, VietnamTel +84918554748Email vothanhtoan1990@yahoo.comAbstract: Epidural abscess after obstetric epidural anesthesia occurs infrequently and may result in severe morbidity. We report a clinical case of an epidural abscess in Vietnam. A 31-year-old woman who was in labor was admitted to our hospital and given epidural anesthesia indicated to relieve labor pain. After three hours of anesthesia, cesarean section was indicated for the patient due to signs of fetal failure, the epidural catheter was then used to relieve pain for the first 48 hours postoperatively. On post-partum day 5 she presented with high fever of 39– 40°C, fatigue, stimulation, dyspnea, and lumbar pain. The patient then suffered from sepsis and lower limb paralysis. She was diagnosed with epidural abscess based on the MRI of the lumbar spine. The abscess was treated by surgery for draining and appropriate antibiotics with a satisfactory outcome as she completely recovered her motor function and stable health status.Keywords: epidural abscess, analgesia, cesarean section